Design and Develop Information Management System for Technical Institute - Mahajan, Sangita; Khare, Priyanks; Kadare, Swapna; Bhandare, Milind (International Journal of Computer Sciences and Engineering, 2025)
Management Information System (MIS) gives information for the activities in an organization. The main purpose of this research is, MIS provides accurate and faster information provide to facilitate the decision-making process and enable the institute planning, control, and operational functionalities to be carried out absolutely. Management Information System (MIS) is basically concerned with processing data into detail information and is then forwarded to the various Departments in an institute for appropriate decision-making. MIS is a subset of the overall planning and control activities covering the application of student technologies, and functionality of the institute. The information system is the m process to ensure that information is available to the administrator in the form they want it and when they need it.